Tick a Box, Any Box: A Case Study on the Unintended Consequences of System Misuse in a Hospital Emergency Department. Issue 2 (November 2015) - Lederman, Reeva; Kurnia, Sherah; Peng, Fei; Dreyfus, Suelette
Long patient waiting periods and a high administrative load plagued the Emergency Department of a major Australian hospital. In response, the department installed a new information system. Technically, the new system worked perfectly. Yet, within 9 months the department suffered a catastrophic loss of patient revenue. The financial disaster led to senior doctors being forced to abandon their medical duties in order to correct complex administrative problems. It triggered a complete review of training, task and role prioritisation. This case study describes a major and costly error resulting from the use of the newly implemented hospital IS. It traces how the error came about, how the hospital responded and what hospitals could do when deploying new systems to prevent such errors. We examine hospitals as hierarchical organisations with financial and organisational goals that sometimes conflict. The case presented explores the cultural setting of the IS roll-out, where medical professionals are accustomed to autonomy over their work practices and are disinclined to engage in activities that they see as interfering with patient care. The case highlights issues in respect to deployment and adoption. These include user training and consideration for the existing organisational culture and stakeholder practices when implementing large systems that cause significant organisational change. The discussion can be structured around stakeholders' behaviour, user resistance, goal conflicts, power shifts, training, division of labour and work flow management. In addition the case raises governance questions: What mechanisms can be used in IT projects to prevent errors like this from arising?